Dose-dependent cytotoxicity evaluation of graphite nanoparticles for diamond-like carbon film application on artificial joints. (24th January 2017) - Liao, T T; Deng, Q Y; Wu, B J; Li, S S; Li, X; Wu, J; Leng, Y X; Guo, Y B; Huang, N
Abstract: While a diamond-like carbon (DLC)-coated joint prosthesis represents the implant of choice for total hip replacement in patients, it also leads to concern due to the cytotoxicity of wear debris in the form of graphite nanoparticles (GNs), ultimately limiting its clinical use. In this study, the cytotoxicity of various GN doses was evaluated. Mouse macrophages and osteoblasts were incubated with GNs (<30 nm diameter), followed by evaluation of cytotoxicity by means of assessing inflammatory cytokines, results of alkaline phosphatase assays, and related signaling protein expression. Cytotoxicity evaluation showed that cell viability decreased in a dose-dependent manner (10–100 μ g ml −1 ), and steeply declined at GNs concentrations greater than 30 μ g ml −1 . Noticeable cytotoxicity was observed as the GN dose exceeded this threshold due to upregulated receptor of activator of nuclear factor kB-ligand expression and downregulated osteoprotegerin expression. Meanwhile, activated macrophage morphology was observed as a result of the intense inflammatory response caused by the high doses of GNs (>30 μ g ml −1 ), as observed by the increased release of TNF- α and IL-6. The results suggest that GNs had a significant dose-dependent cytotoxicity in vitro, with a lethal dose of 30 μ g ml −1 leading to dramatic increases in cytotoxicity. Our GN cytotoxicity evaluation indicates a safe level for wear debris-related arthropathy and could propel the clinical application of DLC-coated total hip prostheses.